Trimetazidine in Heart Failure - Shu, Hongyang; Peng, Yizhong; Hang, Weijian; Zhou, Ning; Wang, Dao Wen (Frontiers in Pharmacology, 2021)
Heart failure is a systemic syndrome caused by multiple pathological factors. Current treatments do not have satisfactory outcomes. Several basic studies have revealed the protective effect of trimetazidine on the heart, not only by metabolism modulation, but also by relieving myocardial apoptosis, fibrosis, autophagy, and inflammation. Clinical studies have consistently indicated that trimetazidine acts as an adjunct to conventional treatments and improves the symptoms of heart failure. This review summarizes the basic pathological changes in the myocardium, with an emphasis on the alteration of cardiac metabolism in the development of heart failure. The clinical application of trimetazidine in heart failure and the mechanism of its protective effects on the myocardium are carefully discussed, as well as its main adverse effects. The intention of this review is to highlight this treatment as an effective alternative against heart failure and provide additional perspectives for future studies.